Enhanced Climate Response to Ozone Depletion From Ozone‐Circulation Coupling. Issue 7 (31st March 2021) - Lin, Pu; Ming, Yi
Abstract: The effect of stratospheric ozone depletion is simulated in GFDL AM4 model with three ozone schemes: Prescribing monthly zonal mean ozone concentration, full interactive stratospheric chemistry, and a simplified linear ozone chemistry scheme but with full dynamical interactions. While similar amounts of ozone loss are simulated by the three schemes, the two interactive ozone schemes produce significantly stronger stratospheric cooling than the prescribed one. We find that this temperature difference is driven by the dynamical responses to ozone depletion. In particular, the existence of ozone hole leads to strong ozone eddies that are in‐phase with the temperature eddies. The coherence between ozone and temperature anomalies leads to a weaker radiative damping as ozone absorbs shortwave radiation that compensates for the longwave cooling. As a result, less wave dissipates at the lower stratosphere, leading to a weaker descending and dynamical heating over the polar lower stratosphere, and hence a stronger net cooling there. The covariance between ozone and temperature is largely suppressed when ozone is prescribed as monthly zonal mean time series, as is the reduction in the radiative damping following ozone depletion. With much lower computational cost, the simplified ozone scheme is capable of producing similar magnitude of ozone loss and the consequent dynamical responses to those simulated by the full chemistry. Plain Language Summary: It is well‐known that the ozone hole over Antarctica leads to a strong cooling in the stratosphere. However, when simulating this effect in climate models, we find that the magnitude of the cooling depends on how ozone is represented in the model. Compared to the model specifying ozone concentrations as monthly time series, stronger cooling is found in the model calculating ozone concentrations from the photochemical reactions. This is because the spatial distribution and the short‐term temporal variation of ozone are not consistent with the circulation when ozone is specified, which leads to a stronger overturning circulation with ascending branch over the tropics and descending branch over the polar region. The stronger descending motion then drives a stronger dynamical heating that compensates for the radiative cooling induced by ozone loss. As a result, a weaker net cooling is produced in the model with specified ozone. We also test a model in which ozone is allowed to vary with the circulation, but the chemical processes are greatly simplified. The computational cost of this model is much cheaper than the one that incorporates the photochemical reactions, but the magnitude of the simulated stratospheric cooling is similar. Key Points: Interactive ozone schemes produce stronger stratospheric cooling than prescribing the same ozone changes Dynamical response to ozone depletion drives the difference in temperature response A cheap interactive ozone scheme is developed and behaves similarly to the full chemistry scheme